Legal Controversy Over Divorce Filed by Wives in Religious Courts in Indonesia - Samsudin, Titin; Sahid, Mualimin Mochammad; Rahim, Arhjayati; Saka, Putri Ananda (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Divorce initiated by a wife is often a source of controversy within religious courts. In line with that, three questions are answered in this paper. First, what is the form of the